Bibliographie über Pupariumparasitoide synanthroper Fliegen. - Klunker, Roland; Fabritius, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1992)
The bibliography contains 1100 papers about pupal parasitoids of synanthropic flies published till 1988. The main emphasis are papers about biology, parasitoid-host-relationships and possibilities of biological control especially with ectoparasitoids from the family of Pteromalidae. In addition some general papers about taxonomy, ecology, rearing methods of parasitoids and side effects of pesticides are received. A subject index is added for a better orientation.